INCREASED CUSTOMER SATISFACTION USING DIGITAL MARKETING IMPLEMENTATION IN THE BANKING INDUSTRY IMAGE - Yoyo Sudaryo; Dayan Hakim Natigor; Rama Chandra Jaya; Nunung Ayu Sofiati (Efi) (Universitas Padjadjaran, 2023)
Digital technology has spread throughout the planet. The banking industry is one that is intimately tied to this technology. The National Private Business Bank (BUSN) employs a variety of digital marketing strategies. One method is to use websites and social media. This study employs a management science method to assess the importance of digital marketing in enhancing customer satisfaction and its influence on banking image. This study use descriptive research methodologies using sample of 140 respondents, with this analysis employing Chou and Bentler’s theory. Finally, the research findings indicate that Digital Marketing Implementation at BUSN has been carried out quite well; in this study, customers at BUSN are satisfied, and the Banking Image at National Private Business Banks (BUSN) has been well obtained. In this study, it is also discovered that Digital Marketing has an impact on Customer Satisfaction at National Private Business Banks (BUSN), with a magnitude of 72.7%. Furthermore, there is a 21.8% effect of Digital Marketing in this study on Banking Image at National Private Business Banks (BUSN), and it is known that there is an effect of Customer Satisfaction on Banking Image at National Private Business Banks (BUSN), with a magnitude of influence of 22.9%, there is an effect of Digital Marketing on Customer Satisfaction, and its Impact on Banking Image at National Private Business Banks (BUSN), with a simultaneous influence of 83.1%, and the remaining 16.9% is influenced by factors other than the research variables.